Coupling of collective excitation in proton and photon interaction with PAHs. (August 2015) - Mishra, P M; Avaldi, L; Bolognesi, P; Prince, K C; Rajput, J; Richter, R; Safvan, C P; Vig, S; Kadhane, U R
Synopsis: Collective excitation in polycyclic aromatic hydrocarbon molecule is studied in collision experiments with intermediate velocity (50-180 keV) proton and FUV (15-40 eV) photon energy. In proton impact experiments a clear comparison between pure ionization and capture ionization (or pure capture) process is done on the basis of ionization, evaporation, fragmentation process as a function of impact energy. Two mechanisms: large impact parameter collective excitation mode and closer encounters with higher amount of electronic energy loss leading to fragmentation were observed in proton collision process. The photon impact results were used to understand the origin of evaporation processes.